Fast curing ethylene vinyl acetate films with dual curing agent towards application as encapsulation materials for photovoltaic modules - W-H. Ruan; H-Y. Xue; M-Q. Zhang; M-Z. Rong (eXPRESS Polymer Letters)
To speed up curing of ethylene vinyl acetate (EVA) films as encapsulation materials for photovoltaic modules, a dual curing agent of benzoyl peroxide (BPO) and butylperoxy 2-ethylhexyl carbonate (TBEC) was introduced in this work. The experimental results indicated that for the weight ratio of BPO/TBEC of 0.6/2.4, over 80% gel content of EVA was yielded after curing at 130°C for 12 min. Compared with the case of single curing agent, the present one obviously operated at much lower temperature with faster rate. By carefully studying the influence of curing agent proportion and curing conditions on gel content of EVA films, as well as rheology and curing kinetics, the mechanism involved was analyzed and verified. The results are believed to be useful for developing new curing system of EVA encapsulation films with improved processability.